Evolutionary processes and cellular functions underlying divergence in Alexandrium minutum. Issue 20 (12th September 2016) - Le Gac, Mickael; Metegnier, Gabriel; Chomérat, Nicolas; Malestroit, Pascale; Quéré, Julien; Bouchez, Olivier; Siano, Raffaele; Destombe, Christophe; Guillou, Laure; Chapelle, Annie
Abstract: Understanding divergence in the highly dispersive and seemingly homogeneous pelagic environment for organisms living as free drifters in the water column remains a challenge. Here, we analysed the transcriptome‐wide mRNA sequences, as well as the morphology of 18 strains of Alexandrium minutum, a dinoflagellate responsible for harmful algal blooms worldwide, to investigate the functional bases of a divergence event. Analysis of the joint site frequency spectrum (JSFS) pointed towards an ancestral divergence in complete isolations followed by a secondary contact resulting in gene flow between the two diverging groups, but heterogeneous across sites. The sites displaying fixed SNPs were associated with a highly restricted gene flow and a strong overrepresentation of nonsynonymous polymorphism, suggesting the importance of selective pressures as drivers of the divergence. The most divergent transcripts were homologs to genes involved in calcium/potassium fluxes across the membrane, calcium transduction signal and saxitoxin production. The implication of these results in terms of ecological divergence and build‐up of reproductive isolation is discussed. Dinoflagellates are especially difficult to study in the field at the ecological level due to their small size and the dynamic nature of their natural environment, but also at the genomic level due to their huge and complex genome and the absence of closely related model organism. This study illustrates the possibility to identify the traits of primary importance in ecology and evolution starting from high‐throughput sequencing data, even for such organisms.